4 (X + 2 (3X - 7)) = 22X - 65
Rearrange the equation by subtracting what is to the right of the equal sign from both sides of the equation:
4 * (X + 2 * (3 * X - 7)) - (22 * X - 65) = 0
Pull out like factors:
7X - 14 = 7 * (X - 2)
28 * (X - 2) - (22X - 65) = 0
Pull out like factors:
6X + 9 = 3 * (2X + 3)
3 * (2X + 3) = 0
3 = 0... (equation never true, has no solution; a a non-zero constant never equals zero)
2X + 3 = 0
Subtract (-3) from both sides of the equation:
2X + 3 (-3) = 0 + (-3)
2X + 3 - 3 = 0 - 3
2X + 0 = -3
2X = -3
Divide both sides of the equation by 2:
2x / 2 = -3 / 2
X = -3 / 2
X = - 1.500